Cross-Salt Extrapolation in the European Union: Regulatory, Scientific, and Strategic Considerations - Joshi, Bhavik L.; S. Kanaki, Niranjan; N. Ahir, Kartik (Journal of Neonatal Surgery, 2025)
Cross-salt extrapolation—the scientific and regulatory practice of bridging non-clinical or clinical data from one salt form of an active pharmaceutical ingredient (API) to another—has gained increasing relevance within the European Union (EU) as pharmaceutical developers seek more efficient product development pathways. This approach holds particular significance in generic drug development, line extensions, and lifecycle management, where re-characterizing an API salt variant can impose substantial time and resource burdens. However, the absence of dedicated EU-level guidelines for cross-salt extrapolation has created a fragmented regulatory landscape, leading to case-by-case assessments and variable expectations across Member States. This article critically examines the scientific rationale and regulatory landscape surrounding cross-salt extrapolation in the EU, including guidance from the European Medicines Agency (EMA), EFSA, and national competent authorities. It delves into the mechanistic and physicochemical considerations that underpin extrapolation viability -such as solubility, dissociation, exposure metrics, and target engagement – whilst also exploring how in-vitro, in-silico, and read-across methodologies are leveraged to justify extrapolation. Furthermore, it discusses strategic considerations for pharmaceutical companies, including risk mitigation, dossier planning, and regulatory communications during procedure selection (CP, DCP, MRP). Through an integrated regulatory – scientific lens, this article proposes a structured approach for enabling cross-salt extrapolation within current EU paradigms and offers recommendations to enhance scientific consistency and regulatory predictability in this under – addressed yet increasingly relevant domain.